Digital culture and e-tourism : technologies, applications and management approaches - Lytras, Miltiadis (New York : Information Science Reference, 2011)
"This edition fosters multidisciplinary discussion and research on the adoption of information and communication technologies (ICT) in the contexts of culture and tourism, investigating how emerging technologies and new managerial models and strategies can promote sustainable development for culture and tourism"--Provided by publisher.
Includes bibliographical references (p. 215-240) and index.
Keywords: Tourism -- Computer network resources; Culture and tourism -- Computer network resources; Heritage tourism -- Computer network resources